Produção de fitase por fungos endofíticos dos manguezais do Estado de São Paulo - Silveira, Lucas de Abreu (2017)
A source of great biotechnological potential for the production of enzymes are endophytic microorganisms. These microorganisms are capable of producing a wide variety of enzymes, among them phytase, which is responsible for phytate hydrolysis. The objective of this work was to evaluate the potential of endophytic fungi of the mangroves of the state of São Paulo for phytase production. Initially, a qualitative selection of 33 isolates with PSM (Phytase Screening Medium) and a second quantitative selection was carried out, in which the preselected fungi were submitted to solid state fermentation (SSF) for phytase production. Among the isolates evaluated, the fungus Aspergillus awamori 9(4) was selected, which presented phytase activity of 43.98 U/100g when submitted to SSF culture for 72 h with soybean meal as substrate. In order to improve phytase production, the use of wheat bran as substrate was evaluated, reaching an activity of 82.77 U/100g, under the same conditions of cultivation. The use of KH2PO4 as an inducer in phytase production and the use of dialysis for the removal of interfering ions from the crude extract in phytase activity were also evaluated. For the experiments performed without the inducer, the dialysis of the extract resulted in activities of 85.42 U/100g with soybean meal and 55.44 U/100g with wheat bran. For the experiments of cultivation with the inductor and then dialysed resulted in activities of 132.35 U/100g with soybean meal and 115.52 U/100g with wheat bran, indicating that the effect of the inducer is positive in the production of Phytase and that dialysis is important for enzyme activity. These results indicate that the endophytic fungus of the mangrove of the State of São Paulo is promising for the production of phytase enzyme, being unpublished the use of endophytic micro-organisms for the production of this enzyme.